The Impact of Food Price Changes and Food Insecurity on Economic Welfare: A Case of Selected Southern African Countries - Giwa, Fiyinfoluwa; Choga, Ireen (Journal of Reviews on Global Economics, 2020)
Households are tremendously affected by changes in food prices. The extent of the impact depends on the income of households. This study is undertaken to analyse the impact of food price changes on food insecurity and economic welfare in selected southern African countries (Lesotho, Malawi, South Africa, Mozambique and Botswana). The Panel Auto Regressive Distributed Lag (PARDL) model is estimated using time series data from the period of 1980 to 2016. The findings of this study showed that food price changes positively affect economic welfare in the long run for the countries. Households that are net food sellers generate a higher income when prices go up. Therefore, food price changes are a gain for these households, especially producers and net sellers. Furthermore, the study revealed that inflation and net trade affect economic welfare for the countries in the short run. As a policy recommendation, the governments of these countries can subsidise food producers, most especially producers of staple foods that are seasonal; this can stabilize food price changes. As a result, both net sellers and net buyers of food can benefit from food prices. In other words, the benefit of food price can spread across to net buyers, not only net sellers. Also the governments of these countries can use monetary policy such as increase in interest rate to combat inflation.